The nine moons of Han Yu and Luli - Glaser, Karina Yan (Allida, an imprint of HarperCollins Publishers, 2025)
"Two eleven-year-olds, one in the China of 731 and the other in Manhattan's Chinatown in 1931, embark on challenging journeys to save their families from peril"-- Provided by publisher.